2019
DOI: 10.21203/rs.2.10785/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic resistance pattern of Staphylococcus aureus with reference to MRSA isolates from pediatric patients

Abstract: Background: Staphylococcus aureus is one of the important superbugs distributed throughout the world. It causes minor skin infections to severe complications including nosocomial infections in both hospitals and community settings. These strains have multi-drug resistant property. Hence, they are difficult to manage which increase health-related costs and simultaneously intensifying the need for new antibiotics. The extent of Methicillin-Resistant Staphylococcus aureus (MRSA) in children is largely unknown. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…For instance, Methicillin resistant staphylococcus aureus (MRSA) detected by a 30 µg cefoxitin disk antibiotic expressed resistance towards cephalosporins, oroquinolones, penicillins and macrolides but were usually susceptible to Vancomycin, Chloramphenicol, Tobramycin, Amikacin, Nitrofurantoin, and Tetracycline. The ndings are supported by other previous studies which also found MRSA expressing 100% resistance to penicillins such as ampicillin and 100% sensitivity to Vancomycin [12]. MRSA as well as the intrinsically resistant Pseudomonas aeruginosa are the common cause of hospital acquired infections that make a successful empirical therapy much more di cult to achieve [25].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For instance, Methicillin resistant staphylococcus aureus (MRSA) detected by a 30 µg cefoxitin disk antibiotic expressed resistance towards cephalosporins, oroquinolones, penicillins and macrolides but were usually susceptible to Vancomycin, Chloramphenicol, Tobramycin, Amikacin, Nitrofurantoin, and Tetracycline. The ndings are supported by other previous studies which also found MRSA expressing 100% resistance to penicillins such as ampicillin and 100% sensitivity to Vancomycin [12]. MRSA as well as the intrinsically resistant Pseudomonas aeruginosa are the common cause of hospital acquired infections that make a successful empirical therapy much more di cult to achieve [25].…”
Section: Discussionsupporting
confidence: 79%
“…Observing antimicrobial resistance (AMR) trends allows for timely identi cation of emerging superbugs as well as developing new interventions, including updating the available national standard treatment guidelines [12]. As part of ensuring full participation in the ght against AMR, Rumphi district hospital antimicrobial stewardships (AMS) committee has been conducting series of AMS activities including participating in global point prevalent survey (GPPS); reviewing and presenting laboratory ndings on AMR and as well as facilitating awareness campaigns to educate healthcare workers on appropriate antibiotics prescribing practices.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial susceptibility profiling, including meticillin susceptibility confirmation using 30-mg cefoxitin disks (Oxoid, Basingstoke, UK), was undertaken as described previously using a panel of 23 antimicrobial agents and heavy metals by disk diffusion using the European Committee on Antimicrobial Susceptibility Testing methodology and interpretive criteria [13,14]. Isolates were deemed to be multi-drug resistant (MDR) if they exhibited resistance to at least three antibiotic classes in clinical use [15].…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…Staphylococcus aureus is very often involved in various types of infections in hospitals and community and especially the methicillin-resistant S. aureus (MRSA) causes a lot of serious health and socioeconomic problems [1,4,7,8,12,13,[15][16][17]. Healthy nasal carriers of S. aureus are estimated to account for approximately 30% of the world's population [10], but some publications suggest that the frequency of nasal carriage of S. aureus is 20 -70%.…”
Section: Introductionmentioning
confidence: 99%